Žodio semantinė struktūra ir leksikografinė praktika - Piesarskas, B. (Kalbotyra, 1973)
The comparative analysis or semantic structure or words in languages L1 and L2 is or utmost importance in lexicography. It may be done by the method or componential analysis, taking into consideration the distributive properties or words, too. When the componential structure or the compared words does not coincide it is important to determine the differential semantic components. In the bilingual dictionary a second equivalent either contains the lacking component or the first equivalent or eliminates its redundant component, The specific lexicographic means is conventionally called the “lexicographic context”.